GIS DATA COLLECTION FOR PEDESTRIAN FACILITIES AND FURNITURE USING MAPINR FOR ANDROID - Naharudin, N.; Ahamad, M. S. S.; Sadullah, A. F. M. (Natural Resources Canada, 2016)
Mobile GIS is introduced to reduce the time taken in completing the field data collection procedure. With the expansion of technology today, mobile GIS is not far behind. It can be integrated with the high-end innovation tools like smartphones. Spatial data capture which deemed to be the toughest stage of a GIS project is made simple with this method. Many studies had demonstrated the usage of mobile GIS in collecting spatial data and this paper discusses how it can be applied in capturing the GPS location of pedestrian furniture and facilities. Although some of the spatial data are available from local agencies, still a more detailed data is needed to create a better data model for this study. This study uses a free android application, MAPinr, which is available on the Google PlayStore to collect spatial data on site. It adopted the GNSS and cellular network positioning to locate the position of the required data. As the application allows the captured data to be exported to a GIS platform, the geometric error of the data was improved. In the end, an authenticated spatial dataset comprising pedestrian facilities and furniture in point and line form will be produced and later be used in a pedestrian network analysis study.